Multitask bilateral learning for real‐time image enhancement - Kong, Kyeongbo; Lee, Junggi; Song, Woo‐Jin; Kang, Minsung; Kwon, Kyung Joon; Kim, Seong Gyun (Journal of the Society for Information Display, 2019)
Nowadays, deep neural networks (DNNs) for image processing are becoming more complex; thus, reducing computational cost is increasingly important. This study highlights the construction of a DNN for real‐time image processing, training various image processing operators efficiently through multitask learning. For real‐time image processing, the proposed algorithm takes a joint upsampling approach through bilateral guided upsampling. For multitask learning, the overall network is based on an encoder‐decoder architecture, which consists of encoding, processing, and decoding components, in which the encoding and decoding components are shared by all the image processing operators. In the processing component, a semantic guidance map, which contains processing information for each image processing operator, is estimated using simple linear shifts of the shared deep features. Through these components, the proposed algorithm requires an increase of only 5% in the number of parameters to add another image processing operator and achieves faster and higher performance than that of deep‐learning‐based joint upsampling methods in local image processing as well as global image processing. This paper proposes a real‐time image enhancement algorithm, based on the encoder‐decoder architecture for multitask learning. The proposed network shares the encoding and decoding components for all image processing operators, and the processing component estimates different semantic guidance maps through a simple linear transformation of the deep feature. The proposed algorithm requires an increase of only 5% in the number of parameters to add another image processing operator and achieves faster and higher performance than that of deep‐learning‐based joint upsampling methods in local image processing as well as global image processing.